2020
DOI: 10.3390/ijerph17124445
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Practices, Satisfaction with Life and the Level of Perceived Stress of Polish and Foreign Medical Students Studying in Poland

Abstract: The adaptation of foreign students to a new country can be complicated due to different cultural values, language barriers and the way university courses are structured. The aim of the study was to analyze the lifestyle practices, satisfaction with life and the level of perceived stress of Polish and foreign students studying various medical disciplines in Poland with regard to chosen sociodemographic characteristics. The study included 231 foreign and 213 Polish students (n = 444) taking different medical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
2
25
1
5
Order By: Relevance
“… 15 Financial instability in the family would be more likely reported as a stressor in high-income group countries, such as Portugal, Italy and Poland, while performance in examinations was the main stressor in Chinese students. 15 , 16 Before the COVID-19 pandemic, online learning has been growing steadily worldwide over the past 20 years resulting in a significant change in the academic environment and the experience of stress among students. 17 Keeping up with information is one of the most cited stressors in online education.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Financial instability in the family would be more likely reported as a stressor in high-income group countries, such as Portugal, Italy and Poland, while performance in examinations was the main stressor in Chinese students. 15 , 16 Before the COVID-19 pandemic, online learning has been growing steadily worldwide over the past 20 years resulting in a significant change in the academic environment and the experience of stress among students. 17 Keeping up with information is one of the most cited stressors in online education.…”
Section: Introductionmentioning
confidence: 99%
“…Higher SWL was observed in respondents with a very good financial situation (M=26.29), lower with good (M=22.84) and bad/ average (M=20.04) [10]. Machul et al (2020) in the group of Polish and foreign students also found that SWL is related to this variable [19]. Czarnecka-Iwańczuk et al (2012) reached the same conclusion.…”
Section: Life Satisfaction Among Women After Vaginal Delivery and Caesarian Sectionmentioning
confidence: 76%
“…Czarnecka-Iwańczuk et al (2012) reached the same conclusion. Lowering SWL was associated with a lower material status, and its higher score determined a greater sense of SWL [20].…”
Section: Life Satisfaction Among Women After Vaginal Delivery and Caesarian Sectionmentioning
confidence: 91%
“…In a Russian study [43], medical and dental students acquired a mean score of 16.97, with gender and socioeconomic status playing a significant role in the differences in scores. Polish medical students obtained a mean PSS score of 22.78 [44]. In another international study of nursing students, Slovak, Polish and Spanish students reported similar mean values for the 10-item PSS score, which indicated moderate stress (Slovak Republic = 18.66, Poland = 18.60, Spain = 18.55) [45].…”
Section: Perceived Stressmentioning
confidence: 86%